Determination of Lead Levels in Soil for Some Areas at East Gezira And Khartoum - Sudan, Africa (Global Journal of Science Frontier Research, 2019)
Lead is a chemical element with an atomic number 82 and symbol Pb and nowadays recognized as a heavymetal poisonous, it affects every system of the body. Acute exposure to a high level of Lead can result in death or significant damage to the brain or other organs. The study aimed to determine the concentration of Lead in Soil of some areas in Khartoum and East of Gezira (Banat, Rufa’a, and Tambol) Specifically. Also, to make a comparison between the rural areas and the urban areas. Eighteen samples of soil havebeen collected from the bus stations, batteries repairing Market in Souk Sha’bi and specific distances away from them. Atomic Absorption Spectrometer method was used to do the analytical work. The concentration of Lead in samples of soil in this Investigation was ranged 0.78 ppm (Banat) – 10.58 ppm (Batteries Market Souk Sha’bi). We found a positive correlation between Urbanization and lead mean concentration of 1.22 ppm in Khartoum and 0.40 ppm in East of Gezira. A positive relationship was additionally found between the concentrations of lead as being closer to the Centre of each one of the transport station and Batteries repairing places and the Main road. So this study recommended that all Leadrelated industries and markets should be far enough from human living to avoid environmental lead pollution.
Keywords: lead pollution; lead poisoning; pollution; environmental pollution; spectro- photometer; aas; and positive correlation